Approach to Small Gastric Subepithelial Lesions - Moon Won Lee; Bong Eun Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Gastric subepithelial lesions (SELs) are often detected incidentally during upper gastrointestinal endoscopy. Although most SELs are benign, endoscopic differentiation between malignant and benign lesions is important. Endoscopy is useful to determine the location, color, consistency, mobility, surface characteristics, and approximate size of gastric SELs. EUS can distinguish between intraluminal lesions and extraluminal compression and confirm the exact size, layer of origin, echogenicity, and homogeneity of SELs. Accurate understanding of the endoscopic and EUS features of gastric SELs is useful to effectively design an appropriate management plan and thereby minimize the rate of unnecessary surveillance or overtreatment.